(untitled) (Journal of Medical & Health Sciences Review, 2025)
Hepatitis C, a viral infection primarily transmitted through blood or body fluids, remains a significant global public health concern. This retrospective study aimed to assess the prevalence of Hepatitis C among dental patients at tertiary care hospitals in Lahore, Pakistan, between June and December 2023. A total of 49 patients, aged 17 to 70 years, were included in the study using a non-probability convenient sampling technique. Data were collected via a self-designed performance that included demographic information, medical history, and results of Hepatitis C screening, including anti-HCV, ELISA, and PCR tests. The findings revealed that 44.9% of the participants tested positive for anti-HCV antibodies, and 40.8% showed detectable HCV RNA in PCR tests. The study highlighted that dental patients are at increased risk of Hepatitis C transmission due to exposure to contaminated instruments, sharps, and blood or saliva during dental procedures. The prevalence of Hepatitis C among dental patients in this study is consistent with previous reports in regions with high endemicity, such as Pakistan. The results underscore the critical importance of implementing strict infection control measures in dental healthcare settings, such as proper sterilization of instruments, the use of personal protective equipment, and routine screening of high-risk patients. Additionally, the study emphasizes the need for increased awareness among healthcare providers and patients regarding the risks of Hepatitis C transmission in dental settings. Future research should focus on larger, multi-centre studies to evaluate the effectiveness of infection control interventions and the long-term outcomes of Hepatitis C-positive dental patients, including their treatment and recovery in clinical practice.